2018
DOI: 10.1038/s41385-018-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus-binding IgG traps HSV in human cervicovaginal mucus across the menstrual cycle and diverse vaginal microbial composition

Abstract: IgG possesses an important yet little recognized effector function in mucus. IgG bound to viral surface can immobilize otherwise readily diffusive viruses to the mucin matrix, excluding them from contacting target cells and facilitating their elimination by natural mucus clearance mechanisms. Cervicovaginal mucus (CVM) is populated by a microbial community, and its viscoelastic and barrier properties can vary substantially not only across the menstrual cycle, but also in women with distinct microbiota. How the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Such weak bonds imply a single antibody is likely incapable of crosslinking a pathogen or particle to mucus. Nevertheless, this weak affinity allows the antibodies to undergo rapid diffusion in hydrogel [26,[39][40][41], and thus quickly accumulate on the surface of nanoparticles and pathogens. In turn, once a critical threshold of antibodies is reached, the array of bound antibodies ensures there is at least one bond between the biogel matrix and nanoparticle-antibody complex at any moment in time, resulting in nanoparticle trapping with permanent avidity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Such weak bonds imply a single antibody is likely incapable of crosslinking a pathogen or particle to mucus. Nevertheless, this weak affinity allows the antibodies to undergo rapid diffusion in hydrogel [26,[39][40][41], and thus quickly accumulate on the surface of nanoparticles and pathogens. In turn, once a critical threshold of antibodies is reached, the array of bound antibodies ensures there is at least one bond between the biogel matrix and nanoparticle-antibody complex at any moment in time, resulting in nanoparticle trapping with permanent avidity [26].…”
Section: Discussionmentioning
confidence: 99%
“…A recently discovered yet little recognized effector function of virus-specific IgG is to crosslink viruses to the mucin mesh [ [69] , [70] , [71] , [72] , [73] , [74] ], leading to their immobilization in AM ( Fig. 2 ).…”
Section: Antibody Function In Airway Mucus (Am)mentioning
confidence: 99%
“…Given the large quantities of endogenous IgG that are already present in airway mucus secretions, inhaled mAb therapies are also likely to be well tolerated. Finally, by harnessing Fc-mucin interactions [ [61] , [62] , [63] , [64] ], inhaled mAbs may also facilitate rapid elimination of viruses from infected airways through mucus clearance mechanisms including muco-ciliary mucus transport and/or cough clearance [ 65 ], thereby physical eliminating the viral antigens that drive pulmonary hyperinflammation. Consistent with the aforementioned advantages of direct delivery into the lung as well as the apical route of infection and spread of these viruses, prior work has shown that human mAbs delivered directly into the lung are highly efficacious [ 58 , 59 , 66 , 67 ], and more effective than the same mAbs introduced systemically [ 58 , 59 ].…”
Section: Systemic Vs Inhaled Delivery Of Antiviral Mab Therapies Usimentioning
confidence: 99%